INNOVATION IN PROCESSING SPINACH (Amaranthus,Sp) PLANT INTO SPINACH JERKY TO INCREASE THE INCOME OF THE COMMUNITY - Dyah Erlina Sulistyaningrum; Tri Rahayuningsih; Suryadi; Fiko Aditya Saputra (Yayasan Putra Adi Dharma, 2024)
This service aims to: (1) Provide new skills training regarding processing spinach (Amaranthus Sp) into spinach jerky to members of the TP PKK Bangunrejo Village, Sukorejo District, Ponorogo Regency. (2) Increasing TP PKK income through processing spinach (Amaranthus Sp) into spinach jerky in Bangunrejo Village, Sukorejo District, Ponorogo Regency. Our type of service is community service. One effort to increase TP PKK's income is by processing spinach (Amaranthus Sp) into snacks that have a higher selling value. Processing of spinach (Amaranthus Sp) is still limited to date. Villagers cultivate a lot of spinach plants, so the quantity of spinach is very abundant, especially in Bangunrejo village. The price of spinach is so cheap that it is not even marketable. Participants in this PKM activity are TP PKK in Bangunrejo Village, Sukorejo District, Ponorogo Regency. The activity carried out was by providing socialization on the benefits and how to make spinach jerky to TP PKK. Provide knowledge about tools for the process of making spinach jerky. Informing about how things work up to the packaging process until it is ready to be marketed. TP PKK in Bangunrejo Village is expected to be able to utilize spinach to make spinach jerky which has a higher selling value, so it is hoped that it can provide benefits in terms of economics and environmental preservation